1994
DOI: 10.2170/jjphysiol.44.391
|View full text |Cite
|
Sign up to set email alerts
|

Non-Insulin and Non-Exercise Related Increase of Glucose Utilization in Rats and Mice.

Abstract: The effects of high-energy phosphate contents in muscles on glucose tolerance and glucose uptake into tissues were studied in rats and mice. Enhanced glucose tolerance associated with depleted high-energy phosphates and elevated glycogen content in muscles and liver was observed in animals fed creatine analogue beta-guanidinopropionic acid (beta-GPA). Distribution of infused 2-[1-14C]deoxy-D-glucose in tissues especially in the soleus muscle, kidney, and brain was greater in mice fed beta-GPA than controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…This tendency for an increase in the mitochondrial enzyme activity of single muscle fibers, combined with an increase in the percentage of slow fibers, is consistent with the enzymatic adaptations seen in whole homogenates of both predominantly fast and predominantly slow muscles [11,14,16,18,21]. Although the activities of most of the glycolytic enzymes are reduced in these muscles [18,21], resting glucose uptake [34] and GLUT-4 glucose transporter expression [18] are increased. Hexokinase activity also is elevated in ␤-GPA-fed rats [21].…”
Section: Discussionsupporting
confidence: 79%
“…This tendency for an increase in the mitochondrial enzyme activity of single muscle fibers, combined with an increase in the percentage of slow fibers, is consistent with the enzymatic adaptations seen in whole homogenates of both predominantly fast and predominantly slow muscles [11,14,16,18,21]. Although the activities of most of the glycolytic enzymes are reduced in these muscles [18,21], resting glucose uptake [34] and GLUT-4 glucose transporter expression [18] are increased. Hexokinase activity also is elevated in ␤-GPA-fed rats [21].…”
Section: Discussionsupporting
confidence: 79%
“…Included studies showed decreased creatine, phosphocreatine, total creatine (creatine+phosphocreatine), and ATP levels of respectively 66.1% (SD 19.2), 79.7% (SD 21.6), 86.7% (SD 10.0), and 38.8% (SD 13.6) after ßGPA (Figure 3 and Figure S1) [11], [12], [20], [22], [25], [31][33], [36], [37], [40], [43], [44], [48]–[51], [53], [54], [56], [57], [62]–[73]. We excluded one study with conflicting results (unchanged creatine, as well as a 56% increase) [71].…”
Section: Resultsmentioning
confidence: 99%
“…Body mass was monitored two times weekly. ␤-GPA was supplemented daily to the diet as described in previous studies (11,21,26,27). Animals were fasted overnight and anaesthetized with an intraperitoneal injection of pentobarbital sodium (5 mg/100 g body mass) before all experimental procedures.…”
Section: Feeding Protocolmentioning
confidence: 99%
“…Increased muscle GLUT4 mRNA and total protein content have been reported in response to ␤-GPA feeding (23,36), and improved insulin-stimulated glucose uptake/clearance in rodent skeletal muscle following ␤-GPA feeding has also been observed (20,21,23). However, there has been no specific assessment of changes in plasma membrane GLUT4 content, which is physiologically more relevant to the process of glucose transport.…”
mentioning
confidence: 99%